Effect of Flipped Classroom Approach (FCA) on Grade 9 Students’ Academic Achievement in the Subject of Chemistry - Hussain, Shahbaz; Butt, Intzar Hussain; Qaisar, Shahzada (Annals of Human and Social Sciences, 2023)
This study aims to explain effect of FCA on grade 9 students’ academic achievement in subject of chemistry and answers research question; is there any effect of flipped classroom approach on academic achievement of Grade 9 students in subject of chemistry? Revised Bloom’s taxonomy for theoretical basis and quasi-experimental non-equivalent two-group research design is used. Grade-9 students of government schools were population of study. 62 students as sample were selected purposively; Groups were selected randomly. The experimental group received FCA intervention. Pretest and posttest is conducted for both groups. Validity of instruments was ensured by three experts; reliability was calculated as 0.70 and 0.86. The study concludes statistically significant difference in pre-posttest scores of both groups. There was large effect size on academic achievement of Grade-9 students after treatment. The researcher recommends that study may be replicated to investigate challenges and hindrances faced by chemistry teachers during implementation of FCA.